Suicide in New Zealand. (2005) - Shahtahmasebi, Said
Abstract : This paper explores and questions some of the notions associated with suicide including mental illness. On average, about two-thirds of suicide cases do not come into contact with mental health services, therefore, we have no objective assessment of their mental status or their life events. One method of improving our objective understanding of suicide would be to use data mining techniques in order to build life event histories on all deaths due to suicide. Although such an exercise would require major funding, partial case histories became publicly available from a coroner's inquest on cases of suicide during a period of three months in Christchurch, New Zealand. The case histories were accompanied by a newspaper article reporting comments from some of the families involved. A straightforward contextual analysis of this information suggests that (i) only five cases had contact with mental health services, in two of the cases this was due to a previous suicide attempt and in the other three it was due to drug and alcohol dependency; (ii) mental illness as the cause of suicide is fixed in the public mindset, (iii) this in turn makes psychological autopsy type studies that seek information from families and friends questionable; (iv) proportionally more females attempt, but more men tend to complete suicide; and (v) not only is the mental health-suicide relationship tenuous, but suicide also appears to be a process outcome. It is hoped that this will stimulate debate and the collaboration of international experts regardless of their school of thought.